Personality Competence of Islamic Religious Education Teachers in Shaping Students' Politeness - Akbar, Rahmadani (Jurnal Kompetensi, 2024)
Education in Islam aims to cultivate good, civilized, and moral individuals, focusing not only on knowledge but also on character development. The personality of the teacher is a key factor in achieving this goal and shaping the students' adab and character, especially in Islamic religious education where manners and morals are emphasized. The success of an Islamic religious education teacher is closely linked to their noble character, serving as a role model and facilitating the teaching and learning process. A qualitative research approach using library research was conducted to explore the personality competence of Islamic religious education teachers in shaping student manners. The findings highlight the importance of the teacher's personality competence, which, when supported by appropriate methods such as habituation, storytelling, and motivation, enables effective teaching and helps shape students' manners. Overall, the teacher's character is vital in achieving educational goals and creating a conducive learning environment for character development.